Auditory Contagious Yawning Is Highest Between Friends and Family Members: Support to the Emotional Bias Hypothesis - Norscia, Ivan; Zanoli, Anna; Gamba, Marco; Palagi, Elisabetta (Frontiers in Psychology, 2020)
Contagious yawning differs from spontaneous yawning because it occurs when an individual yawns in response to someone else’s yawn. In Homo sapiens and some non-human primates contagious yawning is higher between strongly than weakly bonded individuals. Up to date, it is still unclear whether this social asymmetry underlies emotional contagion (a basic form of empathy preferentially involving familiar individuals) as predicted by the Emotional Bias Hypothesis or is linked to a top-down, selective visual attention bias (with selective attention being preferentially directed toward familiar faces) as predicted by the Attentional Bias Hypothesis. To verify whether the visual attentional bias explained the yawn contagion bias or not, in this study we considered only yawns that could be heard but not seen by potential responders (auditory yawns). Around 294 of auditory yawning occurrences were extrapolated from over 2000 yawning bouts collected in free ranging humans for over nine years. Via GLMM, we tested the effect of intrinsic features (i.e. gender and age) and social bond (from strangers to family members) on yawn. The individual identity of the subjects (trigger and potential responder) was included as random factor. The social bond significantly predicted the occurrence of auditory yawn contagion, which was highest between friends and family members. A gender bias was also observed, with women responding most frequently to others’ yawns and men being responded to most frequently by others. Not only these results confirm that social bond is per se one of the main drivers of the differences in yawn contagion rates between individuals, but they also rule out top-down visual attention as the main factor causing the social asymmetry of yawn contagion. Hence, this study supports the Emotional Bias Hypothesis of yawn contagion.